Pancreas‐preserving duodenectomy after living donor liver transplantation for invasive cytomegalovirus disease. (7th September 2017) - Vincenzi, Rodrigo; Fonseca, Eduardo A.; Chapchap, Paulo; Machado, Marcel C. C.; Roda, Karina M. O.; Candido, Helry L.; Benavides, Marcel R.; D'Assuncao, Marco A.; Afonso, Rogerio C.; Turine, Plinio; Marson, Fernando P.; Neto, João Seda
Abstract: CMV infection plays an important role in the postoperative course following solid organ transplantation. We present the case of an 11‐year‐old male patient who underwent LDLT due to severe hepatopulmonary syndrome and biliary cirrhosis. Four weeks after LDLT, he developed persistent GI bleeding and was subjected to repeated endoscopic treatment and radiological arterial embolization to stop the bleeding from duodenal ulcers. Diagnostic workup was negative for CMV disease. Because the bleeding persisted, surgical treatment was indicated, and a pancreas‐preserving duodenectomy was performed. Immunohistochemical staining of the surgical specimen demonstrated diffuse endothelial infiltration by CMV. Despite ganciclovir treatment, the patient developed new erosions in the jejunal mucosa and melena; ganciclovir was discontinued, and foscarnet was started, resulting in clinical improvement and the cessation of bleeding. This case highlights the technical aspects of performing a complex upper GI resection in a patient recently subjected to LDLT, taking care to avoid injury to the previous liver graft anastomosis and restore GI continuity. Moreover, CMV tissue‐invasive disease compartmentalized in the GI tract may be difficult to diagnose, as indicated by the negative results of antigenemia and PCR assays and endoscopic superficial mucosal biopsies.